SCRUTINIZING PAPUAN EFL STUDENTS’ STRATEGIES FOR ENRICHING ENGLISH VOCABULARY MASTERY - Romrome, Abel Yohanis (UC Journal: ELT, Linguistics and Literature Journal, 2024)
The current study aimed to scrutinize the approaches employed by Papuan EFL students to improve their vocabulary skills. The study utilized a mixed methods approach, incorporating both a questionnaire and interviews to gather data from 30 Papuan EFL students enrolled in a private university in Timika, Papua. The results revealed that the majority of participants employed four key strategies for vocabulary acquisition: social, memory, cognitive, and metacognitive. Notably, the memory strategy was most commonly utilized, with participants frequently associating new words with personal experiences to aid in retention. This study provided beneficial recommendations and suggestions for educators. In this sense, the findings of this study can be utilized as useful strategies to teach EFL students based on their interests. Thus, those strategies can facilitate them to achieve vocabulary mastery.